Instalasi dan Pemanfaatan Pompa Hidram untuk Kebutuhan Air Bersih Warga Rumpin Kabupaten Bogor - Candra Damis Widiawaty; Isnanda Nuriskasari; Yuli Mafendro Dedet Eka Saputra; Tatun Hayatun Nufus (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Jakarta, 2026)
Residents of Kampung Candi, Rumpin District, Bogor Regency faced difficulties in obtaining clean water due to the location of the natural water source, which is situated in a lowland area and difficult to access. This Community Service Program was carried out by the lecturers and students of the Energy Conversion Engineering Technology Study Program, Politeknik Negeri Jakarta (PNJ), to provide an appropriate technological solution through the installation of an energy-efficient and environmentally friendly hydraulic ram pump. The activities began with a site survey and elevation measurement of the water source, followed by the design and laboratory testing of the pump, and the installation of the hydraulic ram system in the field. Assistance and training were provided to the community to ensure that residents could operate and maintain the system independently. Survey results showed that more than 90% of residents understood the working principles and benefits of the hydraulic ram pump, while 95% had acquired basic skills in system maintenance. This program successfully improved sustainable access to clean water, strengthened community self-reliance, and supported the implementation of environmentally friendly technology in rural areas.